Dinamika Permasalahan Psikososial Masa Quarter Life Crisis Pada Mahasiswa - Rahma Adellia; Sheilla Varadhila (Universitas Muhammadiyah Gresik, 2023)
Each student show a different response to serve in stages of human development early adulthood. If student don’t serve well, a student will experience quarter life crisis which also causes psychosocial problems arise. The purpose of this study was to determine the dinamic of psychosocial problems in individual facing quarter life crisis. This study uses a qualitative method with a case study approach. The number of participants wa three people and three informants who were close friends of the participants. Data were collected using semi-structures interviews and observations made during the interview process as a complement. The data were analyzed by data reduction, data display, and conclusion drawing. The results show that the ynamics of psychosocial problems in students who are facing a quarter-life crisis begins with the existence of a situation or event encountered that disrupts the psychosocial condition of the participants. Then the participant will try to survive and live the condition until finally the participant cannot do anything. Furthermore, psychosocial problems in participants who face a quarter life crisis have a negative impact both physically and mentally. Responses or ways to deal with psychosocial problems for each participant varied from sleeping, social withdrawal, to smoking. However, the participants continued to live their lives according to their abilities.